Library and Information Science Profession and Curricula: The Employers View Point - Cabutey-Adodoadji, E. (Ghana Library Journal, 1999)
Brian Vickery (1987) has opined that Information Science as an academic discipline is normally constl'-arned by pure scientific understanding of the processes of information transfer. However, when we consider the human , socio-economic activities and the application of information technology it becomes increasingly clear that information service can establish a social foundationfor future development of a world viewpoint. In teaching any discipline, it is necessary to design a curriculum. Curriculum is the planned contents of a programme of study. It encompasses all teaching and learning activities in a prescribed course of study.Indeed curriculum is what is taught and how it is taught. Generally, the instructional programme implies curriculum and its implementation processes, procedure and services. Curriculum development therefore is the improvement of the instructional activities planned and provided by the school system. In essence curriculum development adds value to the original course structurein order to attain the predetermine educationalobjectives.